Quality of Life in Elderly Kidney Transplant Recipients. Issue 10 (3rd October 2014) - Weber, Marc; Faravardeh, Arman; Jackson, Scott; Berglund, Danielle; Spong, Richard; Matas, Arthur J.; Gross, Cynthia R.; Ibrahim, Hassan N.
<x xml:space="preserve">Abstract</x> Objectives To evaluate quality of life (QOL) in kidney transplant recipients aged 65 and older, identify predictors of impaired physical and mental QOL cross‐sectionally and compare QOL over time with that of younger transplant recipients and general population controls. Design Comparison of serial Medical Outcomes Study 36‐item Short‐Form Survey (SF‐36) QOL scores in transplant recipients aged 65 and older with those of transplant recipients younger than 65 and with those of general population controls from the National Health Measurement Study (NHMS). Setting University of Minnesota. Participants Individuals aged 65 and older (n = 150) and younger than 65 (n = 1, 544) who received a primary kidney transplant between 1963 and 2009. Measurements Two‐sample t‐tests and logistic regression were used to assess the risk of significant impairment in physical and mental QOL, defined as 1 standard deviation below the general population norms (<40 points) for the SF‐36 Physical (PCS) and Mental Component Subscale (MCS) scores. Results PCS scores were 39.3 for transplant recipients aged 65 and older, 43.5 for recipients younger than 65, and 49.2 for NHMS controls (P < .005 for each pairwise comparison). MCS scores were 54.6 for transplant recipients aged 65 and older, 51.0 for recipients younger than 65, and 53.8 for NHMS controls (P < .005 for ≥65 vs <65 and NHMS vs <65). These scores did not change significantly from the first (3.6 years after transplant) to the last (6.2 years after transplant) survey. Longer time since transplantation in elderly participants was associated with having significantly impaired physical QOL, but no predictors were associated with significantly impaired mental QOL. In younger recipients, rejection, diabetes mellitus, delayed graft function, coronary artery disease, and longer time on dialysis were associated with impaired physical QOL. Rejection, smoking, diabetes mellitus, and longer time on dialysis were predictors of impaired mental QOL. Conclusion Physical QOL is lower in elderly recipients but mental QOL is maintained and is higher than in younger recipients.